Expression of adropin in rat brain, cerebellum, kidneys, heart, liver, and pancreas in streptozotocin-induced diabetes - Aydin, Suleyman; Kuloglu, Tuncay; Aydin, Suna; Eren, Mehmet Nesimi; Yilmaz, Musa; Kalayci, Mehmet; Kendir, Yalcin (Springer, 2013)
We have investigated how diabetes affects the expression of adropin (ADR) in rat brain, cerebellum, kidneys, heart, liver, and pancreas tissues. The rats in the diabetic group were administered an intraperitoneal (i.p.) injection of a single dose of 60 mg/kg streptozotocin (STZ) dissolved in a 0.1 M phosphate-citrate buffer (pH 4.5). The rats were maintained in standard laboratory conditions in a temperature between 21 and 23 A degrees C and a relative humidity of 70 %, under a 12-h light/dark cycle. The animals were fed a standard commercial pellet diet. After 10 weeks, the animals were sacrified. ADR concentrations in the serum and tissue supernatants were measured by ELISA, and immunohistochemical staining was used to follow the expression of the hormones in the brain, cerebellum, kidneys, heart, liver, and pancreas tissues. The quantities were then compared. Increased ADR immunoreaction was seen in the brain, cerebellum, kidneys, heart, liver, and pancreas in the diabetes-induced rats compared to control subjects. ADR was detected in the brain (vascular area, pia mater, neuroglial cell, and neurons), cerebellum (neuroglial cells, Purkinje cells, vascular areas, and granular layer), kidneys (glomerulus, peritubular interstitial cells, and peritubular capillary endothelial cells), heart (endocardium, myocardium, and epicardium), liver (sinusoidal cells), and pancreas (serous acini). Its concentrations (based on mg/wet weight tissues) in these tissues were measured by using ELISA showed that the levels of ADR were higher in the diabetic rats compared to the control rats. Tissue ADR levels based on mg/wet weight tissues were as follows: Pancreas > liver > kidney > heart > brain > cerebellar tissues. Evidence is presented that shows ADR is expressed in various tissues in the rats and its levels increased in STZ-induced diabetes; however, this effect on the pathophysiology of the disorder remains to be understood.
Keywords: Adropin expression; Immunohistochemistry; STZ-induced diabetes; Rat tissues